Long-term functional outcomes after bladder exstrophy repair: A single, low-volume centre experience - Alsowayan, Ossamah; Capolicchio, John Paul; Jednak, Roman; El-Sherbiny, Mohamed (Canadian Urological Association Journal, 2016)
Introduction: In this study, we present our experience managing bladder exstrophy (BE) in a low-volume centre over 24 years. Methods: Charts of patients with BE between 1990 and 2014 were retrospectively reviewed. Patients with BE closure and ≥5 years followup were included. BE closure was carried out in the first two days of life using either complete primary repair (CPRE) or modernstaged repair (MSRE). Daytime urinary continence (UC) was evaluated by the age of five years. Patients were considered continent if completely dry for ≥3 hours using no or one pad/day. Incontinent patients with bladder capacity (BC) ≥100 ml underwent bladder neck reconstruction (BNR) and bilateral ureteric reimplantation (BUR), while patients with BC <100ml underwent simultaneous augmentation cystoplasty (ACP). Results: Sixteen (16) patients met our inclusion criteria with a mean followup time of 18±5 years. Ten (10) underwent CPRE, while six underwent MSRE. Four surgeons were involved in patients’ management. Two surgeons had previous experience in BE surgery while working in other institutions. Complications included dehiscence in five patients, vesicocutanous fistula in three and breakthrough UTI in eight. Continence was achieved in 15/16 patients: two after BE closure only, seven with BNR, and six who required ACP and BNR. Conclusions: Despite the small number of patients and the reterospective nature of the study, some observations are noteworthy. Although continence rate post-primary BE closure was initially low, it rose to 93.8% after auxiliary continence procedures. This might be at the cost of urethral voiding, which was achieved in 60% of patients. Our small cohort did not show clear advantage of CPRE vs. MSRE. Our outcomes may not be different from high-volume centres due to the fact that two exstrophy-experienced surgeons performed most primary or subsequent surgeries. For this reason, we recommend assigning designated centres for BE repair for both new and repeat cases.